2013
DOI: 10.1038/srep01962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetically modified T2A-1 rice on the GI health of rats after 90-day supplement

Abstract: Bacillus thuringiensis insecticidal toxin (Bt) rice will be commercialized as a main food source. Traditional safety assessments on genetically modified products pay little attention on gastrointestinal (GI) health. More data about GI health of Bt rice must be provided to dispel public' doubts about the potential effects on human health. We constructed an improved safety assessment animal model using a basic subchronic toxicity experiment, measuring a range of parameters including microflora composition, intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…The serum concentrations of TG and TCHO were not affected by the diet treatment. Yuan et al also reported serum concentrations of triglyceride and total cholesterol were similar between Bt and isogenic rice diets fed to the rats for a 90‐day study.…”
Section: Discussionmentioning
confidence: 87%
“…The serum concentrations of TG and TCHO were not affected by the diet treatment. Yuan et al also reported serum concentrations of triglyceride and total cholesterol were similar between Bt and isogenic rice diets fed to the rats for a 90‐day study.…”
Section: Discussionmentioning
confidence: 87%
“…In turn, Zhang et al (2014) and Song et al (2015), obtained also similar conclusions in a long-term toxicity study on transgenic rice, with Cry1Ac and sck genes, and in a 90-day subchronic feeding study of GM rice expressing Cry1Ab protein, respectively, both conducted in SD rats. Yuan et al (2013) determined in SD rats feed with GM T2A1 rice, parameters such as microflora composition, intestinal permeability, epithelial structure, fecal enzymes, bacterial activity, and intestinal immunity. Although significant differences were noted between rice-fed groups and control groups in some parameters, no differences were detected between GM and non-GM groups.…”
Section: Ricementioning
confidence: 99%
“…338F: ACTCCTACGGGAGGCAGCAG and 518R: ATTACCGCGGCTGCTGG were used as primers. Genomic DNA of Escherichia coli with a detection range from 10 3 to 10 12 DNA copies/μl was used to create a standard curve [ 22 ].…”
Section: Methodsmentioning
confidence: 99%